Predictors of Inpatients Mortality in Patients with Liver Cirrhosis with Hepatic Encephalopathy - Bhattarai, Subash; Sharma, Pasanda; Poudel, Sujan Chandra; Tiwari, Ashok; Sapkota, Apil; Gyawali, Merina (Journal of College of Medical Sciences-Nepal, 2024)
Background Hepatic encephalopathy has high risk of recurrence and is associated with advanced cirrhosis of liver. It features a spectrum of reversible neuropsychiatric abnormalities. The purpose of the research was to study the inpatients mortality and its predictors among cirrhotic patients with hepatic encephalopathy. Methods A cross-sectional, hospital-based study comprising of 182 cirrhotic patients with hepatic encephalopathy were evaluated. West Haven Classification (Grade I to IV) was used for grading of hepatic encephalopathy. The data analysis was done using SPSS version 20 and p-value of ≤0.05 was considered significant. Results Majority of patients (39.6%) presented with Grade II encephalopathy followed by Grade III (26.4%). Inpatient mortality was 22.5%. Mortality was seen in 95% patients with HE of grade IV. Univariate analysis showed male sex [p-value=0.01, OR-0.37, CI (0.17-0.820)], shock at presentation [p-value=0.0001, OR-42, CI (16.05 -109.9)], CTP [p-value=0.03, OR-3.8, CI (1.1-13.3)], presence of more than two precipitating factors [P=0.0001, OR-48, CI (10.3-216.3)], presence of SBP [p-value=0.0001, OR-23.4, CI (9.1-60.4)] as statistically significant predictive factors. Multivariate analysis showed shock [P=0.0001, OR-85.3, CI (12.7-571.7)], presence of more than two precipitating factors [p-value=0.0001, OR-101.8, CI (3.32-3119.32)] and SBP [p-value=0.0001, OR-44.7, CI (6.49-309.5)] as statistically significant predictive factors for mortality in patients with liver cirrhosis with hepatic encephalopathy. Conclusions Inpatient mortality was high with increasing grades of encephalopathy among cirrhotic patients. Initial presentation with shock, presence of more than two precipitating factors and SBP were independent predictors of inpatient mortality in patients with liver cirrhosis with hepatic encephalopathy.